Central Bank Asset Puchases I: The Theory - Carolin Raab; Philipp König; Kerstin Bernoth (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In the face of interest rates having hit their zero lower bound in major economies, large-scale asset purchases have become an important weapon of central banks in recent years. It is, however, not clear whether and under which circumstances such policy measures produce the desired effects. This round-up provides a selective overview of theoretical research that has been devoted to understand under what conditions central bank asset purchases lead to reductions in longer-term interest rates and produce stimulating effects on the overall economy.
Keywords: 330